PENGEMBANGAN EKONOMI KREATIF PENGRAJIN BAMBU MELALUI WORKSHOP KERAJINAN BAMBU DESA LAWEYAN KABUPATEN PROBOLINGGO - Vadilla, Icha Tyas Nur; Nur, Dhani Ichsanuddin (Jurnal Pengabdian Masyarakat Sabangka, 2023)
Laweyan Village, Sumberasih District, Probolinggo has a good geographical location with bamboo potential. So it is necessary to utilize the potential of bamboo so that it can develop optimally and has a beneficial value to the people of Laweyan Village. Through creative economic development related to bamboo crafts, bamboo craftsmen can create new innovations and creativity in bamboo crafts. This research aims to develop the potential of bamboo crafts and re-generation of Laweyan Village bamboo craftsmen through bamboo craft workshops. The research method used is descriptive qualitative analysis, by collecting data through observation, survey, and interviews of the object of research. By using a direct approach to the object of research. With bamboo craft workshop activities will open the insight and knowledge of bamboo craftsmen regarding the creative economy related to bamboo crafts. Through bamboo craft workshops will develop innovation and creativity so that it can help improve the economy of the Laweyan Village community.